Biogeochemical cycling of chromium and chromium isotopes in the sub-tropical North Atlantic Ocean - Wang, Wenhao; Goring-Harford, Heather; Kunde, Korinna; Woodward, E. Malcolm S.; Lohan, Maeve C.; Connelly, Douglas P.; James, Rachael H. (Frontiers in Marine Science, 2023)
Chromium (Cr) is a redox-sensitive element and because Cr isotopes are fractionated by redox and/or biological processes, the Cr isotopic composition of ancient marine sediments may be used to infer changes in past seawater oxygenation or biological productivity. While there appears to be a ‘global correlation’ between the dissolved Cr and Cr isotopes of seawater, there is ongoing debate about the relative importance of external sources and internal cycling on shaping the distribution of dissolved Cr. Here, we present full water column depth profiles of total dissolved Cr (Cr(VI)+Cr(III)) and dissolved Cr isotopes (δ53Cr), together with ancillary data, for three stations along a transect (GEOTRACES GApr08) across the sub-tropical North Atlantic. Concentrations of dissolved Cr ranged between 1.84 and 2.63 nmol kg-1, and δ53Cr values varied from 1.06 to 1.42‰. Although atmospheric dust, hydrothermal vents and seabed sediments have the potential to modify the distribution of Cr in the oceans, based on our observations, there is no clear evidence for substantial input of Cr from these sources in our study region. Subsurface waters were very slightly depleted in Cr (by up to 0.4 nmol kg-1), and very slightly enriched in heavy Cr isotopes (by up to 0.14‰), relative to deeper waters and the lowest Cr concentrations and highest δ53Cr values coincided with lowest concentrations of colloidal Fe. We found no direct evidence for biological uptake of dissolved Cr in the oligotrophic euphotic zone or removal of Cr in modestly oxygen depleted waters. Rather, we suggest removal of Cr (probably in the form of Cr(III)) in subsurface waters is associated with the formation of colloid aggregates of Fe-(oxyhydr)oxides. Regeneration of Cr in deeper waters leads to subtly increased levels of Cr alongside decreased δ53Cr values at individual sites, but this trend is more obvious at the global scale, with δ53Cr values decreasing with increasing radiocarbon age of deep waters. Removal of relatively isotopically light Cr from subsurface waters onto particulate material and regeneration of this Cr back into the dissolved phase in deep waters partly accounts for the systematic relationship between δ53Cr and Cr concentrations in seawater discussed by other studies.